Natural hybridization in eastern-Mediterranean firs: The case of Abies borisii-regis. (1st November 2016) - Krajmerová, D.; Paule, L.; Zhelev, P.; Voleková, M.; Evtimov, I.; Gagov, V.; Gömöry, D.
Abstract : The genus Abies is represented in southern Balkans by A. alba, A. cephalonica, and A. borisii-regis . To infer the status of southern-Balkans firs, as well as the extent and patterns of introgression within this taxonomical complex, we analyzed genetic variation patterns of 29 indigenous fir populations in Bulgaria, Macedonia, Greece, and Calabria using a combination of maternally and biparentally inherited markers. Three mitochondrial lineages were observed, one comprising Calabrian populations and two distributed in the Balkans, coinciding with A. alba and A. cephalonica . The boundary between lineages is sharp; only two populations containing a mixture of haplotypes were found. Bayesian analysis of population structure based on seven nuclear microsatellite (nSSR) loci revealed the existence of two clusters whose proportions exhibited a latitudinal cline with a width of 2.3° ( ≈ 255 km). Populations in the center of the latitudinal cline exhibit the most symmetrical, the flattest, and the broadest distributions of cluster proportions within individual tree genomes. A neighbor-net network reflects the cline resulting from the Bayesian analysis. The observed variation patterns are not consistent with the hypothesis of A. borisii-regis as a monophyletic taxon or a stabilized hybridogenous species resulted from ancient hybridization; the taxon rather is a product of recent introgression.